Applying lean manufacturing practices to improve process control in a chemical plant - M. O. Shalnev; Ya. V. Denisova (Омский научный вестник)
This article discusses lean manufacturing methods aimed at improving the management of production processes in a chemical plant. The object of the study is the concept of lean production, the subject is the use of its methods in the production of low fission polyethylene in the public joint-stock company Kazanorgsintez. The article provides a brief overview of the methods and tools of lean manufacturing, which are most widely used in Russian industrial enterprises. Based on the example of low-density polyethylene production in Kazanorgsintez Public Joint-Stock Company, recommendations have been developed on the use of lean manufacturing methods to optimize production processes, in particular, the Just-inTime principle, which is implemented through the use of the automated KANBAN system (at the stage of production of low-density polyethylene) and the "pull" model (on the example of low-density polyethylene storage). As a result of the study, the prospects for the introduction of methods and tools of lean production at a chemical enterprise are shown.